Systemic modeling and relations thinking for risk assessment and IT resources alignment - Papaioannou, Panagiotis; Assimakopoulos, Nikitas A. (Acta Europeana Systemica, 2020)
Systems of any kind expose behaviors that are not directly related to the individual attributes or behaviors of their constituting elements. These are known as emergent behaviors and their existence is a challenge for the manager who oversees an organization or when an intervention is attempted. In this study we argue that interactions or relations provide the main contribution to the existence of the emergent properties and studying these relations can be the starting point for examining or assessing emergent properties or behaviors. Two typical examples of emergent behaviors in an organization which operates as a sociotechnical system are: (a) risk and opportunities and (b) the effectiveness of the information systems. The most systemic organizational paradigms are management systems following an ISO management standard, like ISO 9001:2015. Thus, our approach is aimed at systems of this type.